2009
DOI: 10.1016/j.bpj.2008.12.3891
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation Analysis of Tetanic Rundown (Short-Term Depression) at a Corticothalamic Synapse

Abstract: Hypothetical scenarios for "tetanic rundown" ("short-term depression") of synaptic signals evoked by stimulus trains differ in evolution of quantal amplitude (Q) and covariances between signals. With corticothalamic excitatory postsynaptic currents (EPSCs) evoked by 2.5- to 20-Hz trains, we found Q (estimated using various corrections of variance/mean ratios) to be unchanged during rundown and close to the size of stimulus-evoked "miniatures". Except for covariances, results were compatible with a depletion mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(108 reference statements)
1
4
0
Order By: Relevance
“…Thus, the depletion model predicts a negative correlation between EPSC2 and EPSC1 for two closely spaced stimuli. Consistent with this prediction, a negative correlation between the amplitudes of two closely spaced EPSCs has been observed at the neuromuscular junction (Elmqvist and Quastel 1965), hair cell synapses (Furukawa et al 1978), the calyx of Held (Scheuss et al 2002), thalamocortical synapses (Ran et al 2009), cortical connections (Thomson et al 1993), and hippocampal synapses (Debanne et al 1996). However, at some synapses the extent of depression does not appear to depend on the magnitude of release evoked by the first stimulus (Thomson and Bannister 1999; Kraushaar and Jonas 2000;Chen et al 2004) or the size of the RRP (Sullivan 2007), and an inverse correlation has not been seen at synapses onto Mauthner cells (Waldeck et al 2000) and at hippocampal synapses (Chen et al 2004).…”
Section: Depression the Depletion Model Of Depressionsupporting
confidence: 59%
“…Thus, the depletion model predicts a negative correlation between EPSC2 and EPSC1 for two closely spaced stimuli. Consistent with this prediction, a negative correlation between the amplitudes of two closely spaced EPSCs has been observed at the neuromuscular junction (Elmqvist and Quastel 1965), hair cell synapses (Furukawa et al 1978), the calyx of Held (Scheuss et al 2002), thalamocortical synapses (Ran et al 2009), cortical connections (Thomson et al 1993), and hippocampal synapses (Debanne et al 1996). However, at some synapses the extent of depression does not appear to depend on the magnitude of release evoked by the first stimulus (Thomson and Bannister 1999; Kraushaar and Jonas 2000;Chen et al 2004) or the size of the RRP (Sullivan 2007), and an inverse correlation has not been seen at synapses onto Mauthner cells (Waldeck et al 2000) and at hippocampal synapses (Chen et al 2004).…”
Section: Depression the Depletion Model Of Depressionsupporting
confidence: 59%
“…Modelling studies have shown that synaptic depression increases when the initial release probability and/or frequency of activation are increased ( Dittman and Regehr, 1998 ; Zucker and Regehr, 2002 ; Rizzoli and Betz, 2005 ; Fioravante and Regehr, 2011 ). Indeed, these findings have been found to hold true in glutamatergic cortico-thalamic synapses in a rat brain slices ( Ran et al , 2009 ).…”
Section: Discussionmentioning
confidence: 80%
“…This model predicts that depression will increase when the initial release probability and the frequency of activation are increased. These predictions hold true for many synapses such as corticothalamic synapses and synapses in the auditory brainstem [1,35]. Recovery from depression occurs within several seconds as vesicles from a recycling pool of vesicles replenish the RRP.…”
Section: Depletion Of the Readily Releasable Poolmentioning
confidence: 99%